2021
DOI: 10.3389/fcvm.2021.775307
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Aneurysm and Patient Characteristics on Intracranial Aneurysm Wall Thickness

Abstract: Background: The circle of Willis is a network of arteries allowing blood supply to the brain. Bulging of these arteries leads to formation of intracranial aneurysm (IA). Subarachnoid hemorrhage (SAH) due to IA rupture is among the leading causes of disability in the western world. The formation and rupture of IAs is a complex pathological process not completely understood. In the present study, we have precisely measured aneurysmal wall thickness and its uniformity on histological sections and investigated for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 54 publications
(86 reference statements)
0
4
0
Order By: Relevance
“…Research effort was carried out to measure the material properties of resected IA domes after a clipping surgical operation [ 30 , 70 , 71 ], analyze the alteration of collagen fibre architectures, and report a substantial scatter in ultimate stress and Young moduli between specimens. Even on the surface of a single bulge, it was shown that distinct regions can exhibit very different material properties [ 71 , 72 ]. Although implementing more realistic anisotropic models, such as HGO [ 52 ], does not represent a technical challenge, applying them in a meaningful way is arduous, as the literature does not provide insights into the preferred orientation of fibres in pathological tissue.…”
Section: Discussionmentioning
confidence: 99%
“…Research effort was carried out to measure the material properties of resected IA domes after a clipping surgical operation [ 30 , 70 , 71 ], analyze the alteration of collagen fibre architectures, and report a substantial scatter in ultimate stress and Young moduli between specimens. Even on the surface of a single bulge, it was shown that distinct regions can exhibit very different material properties [ 71 , 72 ]. Although implementing more realistic anisotropic models, such as HGO [ 52 ], does not represent a technical challenge, applying them in a meaningful way is arduous, as the literature does not provide insights into the preferred orientation of fibres in pathological tissue.…”
Section: Discussionmentioning
confidence: 99%
“…While the phenomena observed in this study are consistent with in vivo measurements of aneurysm sounds, experimental studies, and mechanical vibration theory, this is one of the first studies on aneurysm wall vibration and there are some limitations that should be examined to determine their effect on wall vibrations. First, aneurysm walls are known to be non-uniform (Acosta et al 2021 ), which may influence localized wall vibration patterns or full-body mode shapes and frequencies. Also, while adequate to understand the general phenomena, the simple Dirichlet boundary conditions in the current study could be improved using Robin boundary conditions to simulate the surrounding cerebrospinal fluid and other tissue, which would add some damping as shown in Balasso et al ( 2019 ).…”
Section: Discussionmentioning
confidence: 99%
“…Reproduced under the terms of the CC‐BY license. [ 19 ] Copyright 2021, The Authors. b) Types of intracranial aneurysm: i) Saccular: It resembles a rounded outpouching by aneurysmal domes and necks connecting with parent vessel.…”
Section: Introductionmentioning
confidence: 99%
“…ii) View for aneurysm dome.Measuring the location of neck size and maximum dome diameter is depicted. Reproduced under the terms of the CC-BY license [19]. Copyright 2021, The Authors.…”
mentioning
confidence: 99%